Divórcio litigioso: implicações para a parentalidade e a guarda de filhos - Kemerich, Daiane Santos do Carmo (2023)
Divorce can be considered a difficult process for families, as in addition to implying changes and challenges for those involved, it can be a troubled moment and permeated by conflicts. In this sense, it is considered that, when the divorce is litigious, there may be repercussions for the exercise of parenthood and for important decisions such as child custody and their subsequent experience. Thus, this research aimed to understand the experiences of parental pairs about litigious divorce and the implications in the exercise of parenting and child custody decision. To achieve the proposed objectives, qualitative research was used, with the design of multiple case studies, and the epistemological perspective adopted was the paradigm of complexity. Data collection took place through document analysis, characterization forms of the participants, and semi-structured interviews with four parental pairs who went through the litigious divorce process, totaling four fathers and four mothers. The analysis of the data obtained was carried out through the synthesis of crossed cases. The results of this research are presented and discussed in two articles that make up this dissertation. In the first one, it was revealed from the reports of the participants that there could be several reasons that contribute to the establishment of the litigious divorce. In addition, the various repercussions that can occur for family relationships were highlighted. The second article pointed out the losses and challenges that may occur for the exercise of parenting in this context, especially for the coexistence between parents and children, as well as difficulties in establishing and experiencing child custody in the midst of conflicts.